Factors that Shape an Honest and Ethical Culture - Amrullah, Muhamad Tohir; Sari, Martdian Ratna (Asia Pacific Fraud Journal, 2025)
This research aims to identify the factors that shape an honest and ethical culture in the context of fraud prevention. It is important to conduct this research as unethical and dishonest incidents often occur all over the world. The sampling technique was conducted on employees currently working and with work experience in Indonesia, resulting in 200 respondents. Data analysis was performed using Structural Equation Modelling (SEM). The results of this study found that only the tone at the top and effective reward and punishment significantly influenced the formation of an honest and ethical culture. Meanwhile, proper employee recruitment, communication of expectations, and a positive work environment did not significantly impact. This research contributes to stakeholders, especially management considerations, to form an honest and ethical culture within a company.